Molecular and morphological alterations in breast tissue of transgender patients undergoing dihydrotestosterone therapy. - Jinho Lee; Maryam Foroughi; Vanderlene Kung; Rabeka Ali; Saachi Parikh; Ann McMonigal; Yun Yu; Austin Nguyen; Gabriel Zangirolani; Lina Gao; Joanna Pucilowska; Ozlen Saglam (PLoS ONE)
Many patients undergoing gender-affirming surgery (GAS) opt for reconstructive procedures rather than total mastectomy to achieve a more masculine chest contour. The impact of dihydrotestosterone (DHT) treatment on breast tissue remains unclear. This study evaluates the morphological changes and protein expression levels in breast tissue associated with hormonal and molecular pathways in patients receiving short-term or long-term DHT treatment before GAS. A total of 230 breast tissue samples were categorized into three groups: nontreatment, short-term treatment (STT, < 12 months), and long-term treatment (LTT, ≥ 12 months). Paired samples (n = 33) were stained for estrogen receptor (ER) and androgen receptor (AR). NanoString Digital Spatial Profiling (DSP) analysis was conducted on a subset (n = 17), including two incidental breast cancer (BC) cases. Among morphological parameters assessed, atrophy and secretory changes differed significantly among groups. In the LTT group, ER-alpha expression was elevated in lactiferous ducts, while AR H-scores were higher in both STT and LTT groups. ER and AR expression levels were strongly correlated in the STT and LTT groups (r = 0.93-0.99). DSP analysis revealed increased ER expression in the treated groups and higher AR expression in peripheral lobules of the LTT group (log2FC = 1.3, p = 0.03). Ki-67, CDK6, and CD45 levels decreased in the LTT group, while INPP4B and BCL6 increased. DHT treatment leads to significant morphological and molecular changes in both benign and cancerous breast tissue. Altered expression of biomarkers such as INPP4B and CD45 in the LTT group and breast cancer samples suggests a potential role in BC development, warranting further investigation.